1994
DOI: 10.1002/1097-0142(19940501)73:9<2432::aid-cncr2820730929>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of folate receptor isoforms in normal and malignant tissues in vivo and in established cell lines. Physiologic and clinical implications

Abstract: Background. Despite significant differences in ligand binding between the two known isoforms of the human membrane folate receptor (FR), designated herein as FR β (placenta) and FR‐α (placenta, KB cells), little is known about their tissue specificities, and there is no report on the relative expression of FR‐β in any tissue other than in placenta. Methods. The mRNA for each FR isoform in a wide variety of normal fetal and adult tissue explants, primary normal cell cultures, malignant tumor explants, and estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
589
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 858 publications
(602 citation statements)
references
References 30 publications
7
589
0
1
Order By: Relevance
“…This is consistent with previous reports showing that most breast cancers studied had upregulated the folate receptor to some extent, when compared with normal breast epithelial cells. 10 In our series of breast cancers reported here, we saw no correlation between strong FR expression and ER positivity or negativity. This lack of correlation between FR and ER expression was somewhat surprising in view of observations of Ratnam and coworkers that FR expression is repressed in cultured cancer cells in the presence of 17 b-estradiol and derepressed by the antiestrogens tamoxifen and ICI 182780 in promoter-specific and ER-a-dependent manner.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This is consistent with previous reports showing that most breast cancers studied had upregulated the folate receptor to some extent, when compared with normal breast epithelial cells. 10 In our series of breast cancers reported here, we saw no correlation between strong FR expression and ER positivity or negativity. This lack of correlation between FR and ER expression was somewhat surprising in view of observations of Ratnam and coworkers that FR expression is repressed in cultured cancer cells in the presence of 17 b-estradiol and derepressed by the antiestrogens tamoxifen and ICI 182780 in promoter-specific and ER-a-dependent manner.…”
Section: Discussionmentioning
confidence: 51%
“…6 Distribution and binding studies of the high affinity folate receptor have shown high expression in the majority of ovarian cancers, and lesser degrees of positivity in kidney, breast, uterine and lung cancers. [6][7][8][9][10] Studies in ovarian cancer have shown an association between folate receptor overexpression and tumor aggressiveness. 7,[11][12][13] Studies of folate receptor expression in breast cancers have found varying results, depending on the techniques used and tissues analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 The ␣ isoform of the folate receptor (FR), a 38-to 40-kDa glycosylphosphatidylinositol-anchored molecule, 18 -20 is expressed at very low levels on the cell surface of normal epithelial tissues; at medium levels on the kidney, lung, and breast; and at high levels on placental tissue. [21][22][23] Overexpression of FR␣ has been detected on ϳ90% of ovarian carcinomas 23,24 in association with the progression of the disease, 25 on epithelial tumors derived from the uterus, and on nervous system tumors. 22 Based on its expression pattern, FR␣ has been used as a target molecule for monoclonal Ab (mAb)-based immunotherapy strategies.…”
mentioning
confidence: 99%
“…a-FBP, which is recognized by the monoclonal antibody MOv18, is moderately expressed in some normal epithelial cells but is present at higher levels in very specialized organs, such as normal fallopian tubes, adult renal proximal and distal tubules and lactating glands. Moreover, a-FBP is overexpressed in a variety of neoplastic tissues, particularly in non-mucinous ovarian carcinomas (80%) and adenomas (approximately 100%), whereas normal ovary, uterus and vagina are negative (Miotti et al, 1987; Received Veggian et al, 1989;Campbell et al, 1991;Coney et al, 1991;Ross et al, 1994). Such a phenotypic characteristic, although not limited to ovarian carcinomas, may suggest that these neoplastic cells have an increased metabolic requirement for folates, the uptake of which can be highly intensified by an increased expression of the high-affinity FBP receptor molecules.…”
mentioning
confidence: 99%